Proses Entrepreneurship, Kolaborasi Inovasi, Penciptaan Kekayaan di Dalam Organisasi Bisnis - Nizar, Muhammad (Universitas Islam Raden Rahmat, 2017)
Entrepreneurship process is started with innovation. The Innovation is influenced by internal factors and external factors, like education, sociology, organization, culture and environment. This research aims to encourage business organization to grow successfully especially Islamic banking. This research used descriptive analysis to research, evaluate and empower entrepreneurship process, collaboration of innovation and creating wealth in business organization.